The University Classroom, Harassment, and Challenging Provocation. Issue 1 (18th September 2019) - Harless, Jessica
Abstract: The university exhibits particular complexities when it comes to understanding and addressing the gendered harassment that takes place within it. Notions about the nature of higher education and the pedagogical commitments therein can make it difficult to determine the hostility of an environment (a factor crucial to diagnosing harassment). In this article, Jessica Harless taps into some of the vast literature on classroom dialogue, pedagogies of discomfort, and provocative teaching in order to outline difficulties that can arise when attempting to distinguish a challenging learning environment from a harassing one. Harless suggests that rather than relying on descriptive, objective definitions of harassing hostility, we look at subjective factors and the consequences of harassment to try to clarify what it is. Participation, which is expressly protected by Title IX, is one concept available to help gauge the nature of the learning environment. However, the type of participation to be ensured is full participation — unthwarted participant flourishing that goes beyond mere presence or access. This article ultimately focuses on the role and effects of teachers within the classroom environment and highlights a kind of pedagogical commitment that sustains both provocation of challenge and reduction of hostility and harassment.